1993
DOI: 10.1177/10454411930040020101
|View full text |Cite
|
Sign up to set email alerts
|

The Therapy of Oral Lichen Planus

Abstract: Oral lichen planus is a chronic mucocutaneous disease that is relatively common. Although many patients are asymptomatic and require no therapy, those who exhibit atrophic and erosive lesions are often a challenge to treat. All therapies are palliative, and none is effective universally. Currently employed treatment modalities include corticosteroids administered topically, intralesionally, or systemically. Alternative therapies include topical and systemic retinoids, griseofulvin, Cyclosporine, and surgery. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0
15

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 101 publications
(101 reference statements)
1
62
0
15
Order By: Relevance
“…Current treatment may reduce the pain and severity of lesions but is not curative. 38,39 The clinical manifestations and histopathological changes of lichenoid lesions and those for oral lichen planus are similar. Therefore it is important to distinguish between the two groups of lesions since their aetiology and hence their treatment is different.…”
Section: Discussionmentioning
confidence: 73%
“…Current treatment may reduce the pain and severity of lesions but is not curative. 38,39 The clinical manifestations and histopathological changes of lichenoid lesions and those for oral lichen planus are similar. Therefore it is important to distinguish between the two groups of lesions since their aetiology and hence their treatment is different.…”
Section: Discussionmentioning
confidence: 73%
“…Unlike cutaneous lichen planus, OLP tends to be chronic. It has been suggested that complete remission of OLP is either nonexistent or infrequent (see review in Eisen 1993). Histologically, OLP is characterized by a dense bandlike lymphohistiocytic infiltrate in the immediate subepithelial region, with basal epithelial cell destruction.…”
mentioning
confidence: 99%
“…The buccal mucosa, tongue and gingival are the most common sites, whereas palatal lesions are uncommon (2,3). It is seen worldwide, mostly in the fifth to sixth decades of life, and is twice as common in women than in men (1,3,4). OLP is a T cell-mediated autoimmune disease however its cause is unknown in most cases (5).…”
Section: Introductionmentioning
confidence: 99%
“…OLP can present in a number of forms: reticular, plaquelike, papular, atrophic, erosive, and bullous (1,4,6). Reticular, papular, and plaque-like OLP are generally without symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation